Needle sticks and sharps injuries experienced by staff nurses and nursing students and their prevention - Lukianskyte, Ruta; Gataeva, Julija; Radziunaite, Laimute (International Journal of Infection Control, 2011)
The object of this study was to determine the frequency of needle sticks and sharps injuries (NSIs), to assess and compare the reasons and factors affecting NSIs experienced by staff nurses and nursing students and to define how they were informed about notification and prevention of NSIs. In 2010 staff nurses and nursing students performing invasive injections at the Republic Hospital of Kaunas participated in the survey. Two hundred fifty questionnaires were distributed, of which 196 were returned giving a response rate of 78.4%.During the 12-month study period, NSIs were experienced by 38.5% of staff nurses and 78% of nursing students. Activities occurring in procedure rooms presented the highest risk of experiencing a needle stick or sharps injury. For nurses, fifty-one percent (51%) sustained their injuries when putting a case on a used needle (recapping). Forty-nine percent (49%) of the nursing students experienced an injury when breaking an ampoule. Prevailing reasons for injuries were inattentiveness, being in a hurry and work overload. More of the staff nurses (96.9%) than the nursing students (40%) were familiar with the rules of NSIs notification, registration, observation and prevention. Among staff nurses, 45.9% of the occurrences were unreported while for nursing students 92.0% were unreported. Only 16.9% of staff nurses and 11% of nursing students were vaccinated with three doses of HBV vaccine.This study showed that more attention should be given to notification of needle stick and sharps injuries among nursing students. Immunization of staff nurses and nursing students with hepatitis B vaccine should also be encourage and recommended.